Integrated SubmmWave Receiver: Development and Applications - Koshelets, Valery P.; Birk, Manfred; Boersma, Dick; Dercksen, Johannes; Dmitriev, Pavel; Ermakov, Andrey B.; Filippenko, Lyudmila V.; Golstein, Hans; Hoogeveen, Ruud W.M.; de Jong, Leo; Khudchenko, Andrey V.; Kinev, Nickolay V.; et al. (Springer-Verlag Berlin Heidelberg, 2011)
A superconducting integrated receiver (SIR) comprises in a single chip a planar antenna combined with a superconductor-insulator-superconductor (SIS) mixer, a superconducting Flux Flow Oscillator (FFO) acting as a Local Oscillator (LO) and a second SIS harmonic mixer (HM) for the FFO phase locking. In this report, an overview of the SIR and FFO developments and optimizations is presented. Improving on the fully Nb-based SIR we have developed and studied Nb–AlN–NbN circuits, which exhibit an extended operation frequency range. Continuous tuning of the phase locked frequency has been experimentally demonstrated at any frequency in the range 350–750GHz. The FFO free-running linewidth has been measured between 1 and 5MHz, which allows to phase lock up to 97% of the emitted FFO power. The output power of the FFO is sufficient to pump the matched SIS mixer. Therefore, it is concluded that the Nb–AlN–NbN FFOs are mature enough for practical applications. These achievements enabled the development of a 480–650GHz integrated receiver for the atmospheric-research instrument TErahertz and submillimeter LImb Sounder (TELIS). This balloon-borne instrument is a three-channel superconducting heterodyne spectrometer for the detection of spectral emission lines of stratospheric trace gases that have their rotational transitions at THz frequencies. One of the channels is based on the SIR technology. We demonstrate for the first time the capabilities of the SIR technology for heterodyne spectroscopy in general, and atmospheric limb sounding in particular. We also show that the application of SIR technology is not limited to laboratory environments, but that it is well suited for remote operation under harsh environmental conditions. Light weight and low power consumption combined with broadband operation and nearly quantum limited sensitivity make the SIR a perfect candidate for future airborne and space-borne missions. The noise temperature of the SIR was measured to be as low as 120K in double sideband operation, with an intermediate frequency band of 4–8GHz. The spectral resolution is well below 1MHz, confirmed by our measurements. Remote control of the SIR under flight conditions has been demonstrated in a successful balloon flight in Kiruna, Sweden. Capability of the SIR for high-resolution spectroscopy has been successfully proven also in a laboratory environment by gas cell measurements. The possibility to use SIR devices for the medical analysis of exhaled air will be discussed. Many medically relevant gases have spectral lines in the sub-terahertz range and can be detected by an SIR-based spectrometer. The SIR can be considered as an operational device, ready for many applications.